The pivotal role of protein acetylation in linking glucose and fatty acid metabolism to β-cell function - Zhang, Yuqing; Zhou, Feiye; Bai, Mengyao; Liu, Yun; Zhang, Linlin; Zhu, Qin; Bi, Yufang; Ning, Guang; Zhou, Libin; Wang, Xiao (Cell death & disease, 2019)
Protein acetylation has a crucial role in energy metabolism. Here we performed the first large-scale profiling of acetylome in rat islets, showing that almost all enzymes in core metabolic pathways related to insulin secretion were acetylated. Label-free quantitative acetylome of islets in response to high glucose revealed hyperacetylation of enzymes involved in fatty acid β-oxidation (FAO), including trifunctional enzyme subunit alpha (ECHA). Acetylation decreased the protein stability of ECHA and its ability to promote FAO. The overexpression of SIRT3, a major mitochondrial deacetylase, prevented the degradation of ECHA via decreasing its acetylation level in β-cells. SIRT3 expression was upregulated in rat islets upon exposure to low glucose or fasting. SIRT3 overexpression in islets markedly decreased palmitate-potentiated insulin secretion, whereas islets from SIRT3 knockout mice secreted more insulin, with an opposite action on FAO. ECHA overexpression partially reversed SIRT3 deficiency-elicited insulin hypersecretion. Our study highlights the potential role of protein acetylation in insulin secretion.